Pengaruh Intellectual Capital dan Financial Stability Terhadap Kinerja Harga Saham: Kualitas Audit Sebagai Moderasi - Riris Rotua Sitorus; Nurry Syuhadah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This study aimed to determine and analyze the influence of intellectual capital, financial stability on stock price performance with audit quality as moderating. The sample used in this study was a consumer goods sector company listed on the Indonesia Stock Exchange for the period 2014-2019. The populations in this study were 52 Consumer goods companies. Purposive sampling was used as a sampling technique so that the total samples used were 18 companies in the consumer goods sector. The method used in this study was a quantitative method which can be obtained by calculating and recording secondary data from the financial statements on the IDX for the 2014-2019 period. The results of this study stated that intellectual capital had effect on stock price performance, financial stability and audit quality had no effect on stock price performance. For moderating, audit quality can moderate the effect of intellectual capital on stock price performance, while audit quality can not moderate the effect of financial stability on the performance of stock prices. Based on these results, recommendations for further research are expected to modify the research model and increase the research period.